INTEGRATION OF RESERVOIR SIMULATION, SURFACE FACILITIES AND ECONOMIC FOR DEVELOPMENT PLAN STUDY OF A GAS FIELD CONTAINING HIGH CO2 & H2S BY CONSIDERING THE RISK FACTOR - TOHA (NIM : 22207010), AHMAD
The plan of field development or POD will be very important document considering as a main parrent reference for the implementation in term of spending cost, both in the Work Plan and Budget (WP&B) and the Authorization for Expenditure (AFE). Therefore, the comprehensive and integrated studies are required to get a solid and up to date document for the references. This study is a detailed research of plan of gas field development which has the high CO2 and H2S content. This study is conducted covering a detailed subsurface evaluation (starting from geological model, reservoir simulation, development scenarios), surface facilities evaluation (required facilities design for handling high pressure acid well stream and the required estimated cost), and economic evaluation including spending schedule and project economic parameters. This integrated analysis hopefully find the optimum plan of field development. Based on the geological modeling and reservoir simulation, found that AS field which consist of sour gas (CO2 27.5% & H2S 1.2%) has reserves up to 360 BCF with the recovery factor of 81%. Combined with development of AR field which is relatively more sweet (CO2 11% & H2S ≈ 0%), the peak rate of 110 BBTUD is reached for 4.3 years and the rate of 55 BBTUD for 2.7 years for fertilizer plant, while the tail gas of 15 BBTUD will be delivered to supply the contract of Power plant. Considering the high impurities content, the gas plant requires gas sweeting process using MDEA as a solvent. The gas dehydration unit required using TEG as water absorbent. Dew point control system is mechanical refrigeration with Propane (C3) as refrigerant. Acid conversion unit is modeled as Ã‚Â„Claus‟ process. The simulation indicating that the operating pressure for the CPP is 990 psig through out the life, therefore AS CPP need to be designed for 600 psig rating as minimum. Economic analysis conducted to evaluate the uncertainty of reserves using Low, Mid dan High case for 2 development Scenarios; i.e. development 1-fase 2-train (55 bbtud form AR only & directly ramp-up to 110 bbtud soon after the AR decline) and development 2-fase 2 train (55 bbtud form AR and then AS and the capacity will ramp-up to 110 bbtud after the all capacities of AS completed). Other additional Scenario is considering development of 55 bbtud flat for the life of the field anticipating the shortfall Scenario. Run economic results indicates the Scenario-1 (1 Fase Ã‚Â– 2 Train) has NPV & IRR better than the Scenario-2 (2 Fase Ã‚Â– 2 Train). The IRR of Scenario-1 is 21.9%, higher than Scenario-2‟s IRR (20.1 %), or the NPV of Scenario-1 is $70.0 million while the NPV of Scenario-2 is $52.7 million. The decision tree analysis indicates the Scenario-2 has a lower risk compared to the Scenario-1, where the NPV of Scenario-2 ($38.2 million) higher than the NPV of Scenario-1 ($34.0 million). The shortfall case, Scenario-3 still has a good economic result with the IRR is 21.6 % and NPV is $ 61.9 million.